Public speaking for criminal justice professionals : a manner of speaking - Mauriello, Thomas P. (Boca Raton, FL : CRC Press, Taylor & Francis Group, 2021)
"Public Speaking for Criminal Justice Professionals: A Manner of Speaking is the first of its kind public speaking guide specifically written for criminal justice professionals, written by a criminal justice professional. Author Thomas Mauriello has worked his entire professional career both as a practitioner and as an educator in the fields of criminal justice and forensic science. This book would identify the public speaking skills he has learned, used, and taught to thousands of criminal justice, forensic science, security, and counterintelligence professionals over the years. A Manner of Speaking will improve the reader's presentation skills whether they are preparing to speak to one or one thousand people. It will improve the skills of the experienced speaker while providing a basic foundation for the beginner. The book will include techniques for speaking with confidence, choosing the right audio-visual technologies, and how-to strategies for satisfying the needs and expectations of an audience. 55+ proven effective presentation tools will be listed, discussed, and demonstrated throughout the book using illustrated criminal justice and forensic sciences topic examples. Knowing your subject or being an expert in the subject does NOT guarantee a successful presentation. Aristotle, who many recognize as the Father of Public Speaking and Forensic Debate said it best when he declared, "It is not enough to know what to say, one must know how to say it." This guide would focus on technique and the recognition that a speaker must focus on both the subject and the listener. The purpose is to both engage and, thereby, inform the listener. This book is written to either be read from cover-to-cover-to fine tune the reader's existing oral communication skills-or read in a modular, as a reference guide to focus on certain skills and techniques. It can be used by both criminal justice professionals, but equally by professionals in other fields since the same skills and understanding is required in nearly all disciplines"--
OCLC-licensed vendor bibliographic record.
Keywords: Criminal justice, Administration of; Public speaking; Forensic oratory; Communication in law; Communication in law enforcement; LAW / Criminal Law / General; SOCIAL SCIENCE / Criminology